Learning meant as conscience refinement in contemporary society - Arioli, Antonella (Formazione & insegnamento, 2015)
Putting at the center of its thought the man’s need of sense and the will of meaning as original motivation of its intrinsic educability, Viktor Emil Frankl’s Logotherapy represent the antrhropological foundation of an education intended as an answer for the needs of formation of our times, forwarding a concept of learning as an improvement of that organ of sense which is the conscience, able to reveal the meanings contained into the single existential situations.